DEHUMANIZED & OBJECTIFIED WOMEN IN SOMALY MAM AND RUTH MARSHALL’S THE ROAD OF LOST INNOCENCE - Hana Farida; Fadhila Faiza Amalia (Lire Journal)
This research attempted to understand how dehumanization along with objectification occurred in prostitution. Dehumanization occurred when people treated others less than humans by denied their human uniqueness and nature and added negative attributes to refer to them as animals or objects. This research discussed how the victims of prostitution suffered dehumanization and how this dehumanization affected the victims, positioning them as objects, as portrayed in Somaly Mam and Ruth Marshall’s The Road of Lost Innocence. This research is qualitative-descriptive research. The main data is Somaly Mam and Ruth Marshall’s The Road of Lost Innocence, while supporting data is obtained from books, articles, and journals. In analyzing the data, the researcher applied the dehumanization theory of Haslam and the consequences of dehumanization as described by Bastian and Haslam. The results of this research showed the victims of prostitution suffered dehumanization based on Haslam’s theory: first, animalistic dehumanization, where the brothel owner viewed victims as animals, trained the victims as animals, etc. Second, mechanistic dehumanization occurred when a victim was sold into the brothel by her family, and the owner of the brothel treated the victims like goods that could be traded, etc. This researcher also discovered that this dehumanization affected the victim's cognitive and emotional responses.